Virtual guard - Mohamad Faiz, Mohd Ali (2010)
This project entitle VIRTUAL GUARD is one of the general-purpose of computer-based closed circuit television(CCTV) surveillance system that use to detect intruder in private or restricted area by applying the image processing technique of detecting object. Ordinary CCTV can only be used to record incidents if it does occur. It works without preventing it and it is only useful to be an evidence for the investigation. But the purpose of developing this project is as the earlier prevention to avoid crime by giving alert or feedback from the object that was detected from captured video. In order to achieve the goal of this project, a few techniques in image processing will be use like image subtraction technique which is use to detect movement and object existence like an intruder which has been captured in the video. The captured video in this project will be convert into frame of images and being analyze by using MATLAB software that already consist all the techniques of image processing. The output of this project will be classified if there is any detection or not by using the value of total sum of pixel value from each image data. The classification is actually based on the threshold value. This project indirectly reduce weakness and careless of human guard observation as it give continuous 24-hour monitoring of surveillance video to alert security officers to an intruder potential.